Perilaku Konsumtif Mahasiswa dalam Membeli Produk Fashion - Hasan, Muhammad; Tahir, Thamrin; Inanna, Inanna; Supatminingsih, Tuti; Arisah, Nur (Phinisi Integration Review, 2021)
The student's decision to consume an item is also influenced by the student's personal characteristics. This research is a descriptive quantitative approach with survey techniques and online interviews using questionnaires filled out online using google form. There are five variables that are measured to determine the consumer behavior of students in buying fashion products, including: cultural factors, reference groups, roles and status, lifestyle, and learning. The population in this study were students of Economics Education, Faculty of Economics and Business, Makassar State University, batch 2019-2020, totaling 222 students. The sample amounted to 70 students. Based on the research data, it is known that the influence of cultural factors on the purchase of fashion products is 47.15%, the influence of reference group factors on the purchase of fashion products has a percentage of 72.62%, the influence of role and status factors has a percentage of 73.86%, the influence of style factors living has a percentage of 71.42%. And the influence of learning factors is 55.59%. So the role and status factors, reference groups, and lifestyle factors are more dominant that influence the consumer behavior of students in buying fashion products. Meanwhile, in simple linear regression analysis, the research results show that the research results prove that the variable that has a dominant influence on the fashion product purchase variable (Y) is the reference group variable (X2) where the regression coefficient value (Î²) is 0.368 it can be concluded that the reference group variable (X2) is the variable that has the most dominant influence on the variable purchasing fashion products (Y).